Positive effect of fermented sorghum on productivity, jejunal histomorphology, and tight junction gene expression in broiler chickens - Patrick Erhard Latue; Bambang Ariyadi; Asih Kurniawati; Muhsin Al Anas (Poultry Science)
This study aimed to investigate the effects of dietary fermented sorghum (FS) as a substitute for corn on growth performance, jejunal histomorphology, cecal short-chain fatty acid (SCFA) levels, and gene expression of tight junctions in broiler chickens. A total of 240 one-day-old male New Lohmann Indian River chicks were randomly divided into five groups, with each group receiving different dietary treatments: a control group (CTRL) with a basal diet, groups supplemented with 10% (NFS10) and 20% (NFS20) non-fermented sorghum, and groups supplemented with 10% (FS10) and 20% (FS20) fermented sorghum. Each group was further divided into six replications, with eight birds per replicate. Orthogonal contrasts were used to compare the feed treatments (fermented sorghum and non-fermented sorghum) to the control. The results revealed that the inclusion of 20% fermented sorghum significantly increased feed intake (FI, P = 0.005), body weight (BW; P = 0.025), and body weight gain (BWG; P = 0.010) compared to other groups. Additionally, the FS20 group exhibited a notable increase in villus height (P = 0.001). There were significant differences in cecal short-chain fatty acid (SCFA) production among the treatment groups (P < 0.05). Furthermore, fermented sorghum notably upregulated the gene expression of occludin (OCLN, P = 0.008), without significant impacts on the expression of claudin-1 (CLDN-1), junctional adhesion molecules-2 (JAM-2), and zonula occludens-1 (ZO-1). In conclusion, addition of 20% fermented sorghum in broiler diets could enhance growth performance and intestinal histomorphology, indicating its potential as a beneficial feed ingredient for poultry production.